An econometric analysisof the impactof Syrian refugees on crime in Turkey - Türküm, Fatma Betül. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2018)
A common apprehension is that im.rrllgration raises crime rates. Yet, existing academic research has revealed no such outcome. Past and current studies discover that at the individual level, immigrants are not more prone to involve in criminal activities than the native-born. Notwithstanding general criticism claimino a linkaoe 1:> 1:> between immigration and crime, empirical research examining this relationship is inadequate, particularly at the macro-level. To address this matter, this study exa.rrllnes the link between migration and crime rates across Turkey's provinces with the Differences-and-Differences methodology. Using panel data on provinces, this paper presents empirical evidence on the impact of immigration on crime. After controlling for the demographic and economic characteristics of the provinces, I find that inunigration does not increase total crime rates. Yet, the Syrian refugee density has an increasing impact on the crime of smuggling, which is a crime motivated by financial gains. Because smuggling represents a small part of all crimes, the effect on the overall crime rate is not significant. I also find that there is a significant negative impact of the Syrian refugee density on the number of crimes committed by females, especially the crime of assault.
Keywords: Refugees -- Turkey.; Crime -- Turkey.